2017
DOI: 10.22159/ajpcr.2017.v10i7.18633
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Study Evaluating the Knowledge, Attitude of Undergraduate Medical Students About Pharmacovigilance and Adverse Drug Reaction Reporting at a Medical College in Hyderabad

Abstract: Objectives: Objectives of the study were (1) to evaluate the knowledge about pharmacovigilance and (2) to assess the attitude toward adverse drug reaction (ADR) reporting among undergraduate medical students.Methods: It is a cross-sectional, questionnaire-based study conducted in the Department of Pharmacology, Malla Reddy Medical College for Women, Hyderabad, Telangana, among fifth term Bachelor of Medicine, Bachelor of Surgery students (136). The questionnaire consisted of 16 questions dealing with knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Similar findings are seen in other studies. 16,17 Furthermore, 89.7% of respondents thought that ADR monitoring and reporting center should be there in all teaching hospitals. A study in India reported that only 46.9% of participants thought that establishing ADR monitoring center in every hospital was necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings are seen in other studies. 16,17 Furthermore, 89.7% of respondents thought that ADR monitoring and reporting center should be there in all teaching hospitals. A study in India reported that only 46.9% of participants thought that establishing ADR monitoring center in every hospital was necessary.…”
Section: Discussionmentioning
confidence: 99%